Efek Rebusan Daun Tapak Dara pada Dosis dan Frekuensi yang Berbeda terhadap Kerusakan dan Akumulasi Glikogen pada Hepar Mencit (Mus musculus) - Dewi, Utari Kusuma; Saraswati, Tyas Rini (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2009)
The aim of this research was to investigate the effect of boiled -Vinca rosea leaf for hepar and glycogenaccumulation in Mus musculus hepatocyts on several dosages, frequencies and the interaction of dosagesfrequencies.The research used factorial experiment with Complete Randomize Design and continued with Duncan test at5% level. The result of this experiment indicated that there was significant by different of dosage treatment. Thehigher dosage boiled- Vinca rosea leaf that given into Mus musculus, the more hepatocyts damage. Hepatocyt injurywas indicated by swollen until atrophy cell with glycogen accumulation in the cytoplasm of hepatocyt.